A local assessment of the impacts of fifteen years of BMCT interventions - Wieland, Michelle; Bitariho, Robert (BWINDI MGAHINGA CONSERVATION TRUST, 2013)
This Assessment Project was solicited by the Bwindi Mgahinga Conservation Trust (BMCT, hereafter referred to as the Trust) to examine impacts of Trust interventions in the Bwindi and Mgahinga Conservation Area (BMCA) and identify the most successful and appropriate interventions in order to advise on future interventions in the BMCA. The Trust, working since it was created in 1997, has taken up a key role as a leader for integrated conservation and development projects (ICDs) around BMCA. As one of the first trust funds set up in Africa, it has been engaging in common goods projects, livelihood development for rural people around the park, and is acknowledged as contributing to the improvement of attitudes since Bwindi and Mgahinga were created. Through this assessment, it continues to be a leader in ICDs through examining its own activities, the governance of its projects, and its continuous improvement through review. This assessment focused on impacts over the past fifteen years in Trust’s 3 pillars of support: Park, Research, and Community Projects (subdivided into: Batwa, Livelihoods, common goods, conservation with communities, and Awareness/Outreach projects. Data on these projects were collected between October and December 2012, in 18 of the 56 parishes that the Trust works with. We conducted 306 surveys with local government, Batwa, Local Community Steering Committee (LCSC) representatives, community members, and past/present members of the Institute of Tropical Forest Conservation (ITFC) and the park managers from the BMCA to give a broad and solid picture of the community perspective of actual impact in Bwindi Mgahinga region regarding the Trust interventions. In addition to the impact assessment this activity also developed a database for Trust interventions and produced maps showing the Trust project interventions in the BMCA to help the Trust Administration Unit (TAU) spatially visualize the projects and interventions in the BMCA over the past fifteen years. This assessment focused on Trust interventions of impacts on community wellbeing and conservation (awareness and attitudes leading to change in behaviors of local people). We define ‘impacts’ as the stakeholders’ perceptions of benefits from Trust projects and their links to conservation. In general, the local people recognize the contributions of the Trust interventions towards their livelihoods. Given the high population around BMCA, the overall conservation impact, particularly for livelihood projects in non-Batwa communities, is small. However, larger projects such as schools and the Banyara gravity scheme have benefitted villages across the BMCA. Likewise, land acquisitions and livelihood projects are important Trust projects for the Batwa. The reason ICDs benefit local people is to, indirectly, contribute to conservation goals of protected areas. This linkage in BMCA though weak was apparent and depended on the type of Trust interventions. Local people awareness and attitudes towards the conservation of BMCA as a result of Trust projects have greatly improved, and people reported that it has changed their behaviors. However, because this Assessment did not measure conservation targets, we cannot directly measure how people’s awareness and attitude change has led to changes in actual behaviors towards illegal resource extraction from the park. completely change people’s illegal resource use without stronger targeting of projects to illegal resource users and to address the drivers of this behavior. Project successes vary by location. Batwa projects have been well received, particularly land purchases that completely transformed their lives. Common goods projects impact many people, and are generally seen as successful in contributing to wellbeing. However, the Batwa feel livelihood projects funded by the Trust are more beneficial to them than common good projects. Batwa recognize the Trust-funded projects such as land acquisition for them but most of them feel they do not own the land. The Batwa sense of ownership projects were more felt in the livelihood improvement projects than the common good projects. Beneficiaries are appreciative of Trust livelihood projects and they are popular with local people. However, the small investment in each livelihood beneficiaries group, compared to the operating costs in carrying out an overall livelihood program with relatively few people who benefit, suggests the Trust may want to reconsider the way they support local livelihoods. Finally, conservation projects with local people, such as tree planting, have been incredibly successful, both at providing alternative sources of firewood and increased household income, but also in the conservation of village lands from erosion. When examining how the Trust implements programs, we have found two issues that should be addressed. Although general governance is relatively good (project ownership and participation), the Local Community Steering Committee (LCSC) system needs attention. Participation of local people in the Trust and Trust livelihood projects is weak due to the lack of mobility of LCSCs to the village and the existence of representation of villages in the system. The result is that the livelihood system lacks transparency, nearly half the villagers do not know how to apply for Trust projects, and elite capture of resources can weaken the ability of the Trust to alleviate poverty through this program. The second issue with implementation is the complete lack of a monitoring and evaluation (M /E) system. The Trust is rolling out an M/E system this year, which is critical for the Trust to be able to ensure the sustainability of its interventions. Having an M/E system that gathers information each year will contribute to the Trust’s impact, and allow it to conduct meaningful assessments every 5 years. This assessment review has been a large endeavor, containing a lot of information for the Trust to digest. The report is divided into 3 main sections. Chapter 1 provides an introduction to the Assessment. Chapters 2-4 present the Assessment findings, followed by a discussion in Chapter 5. To conclude, Chapter 6 synthesizes the multitude of recommendations from our 306 interviews with our observations and understanding of Trust constraints, to provide a list of suggestions on how the Trust could move forward to work on projects with the park, with research, and with the local people. We conclude with a compact version of what we highly recommend the Trust focus on over the next two years as the legacy of the Trust continues to be built. Repeated, they include the creation of/focus on:  BMCA Emerging Needs Fund for targeted projects  Short and long-term research plan development with ITFC and BMCA  Support PAM initiatives with direct links to local livelihoods and conservation  Awareness strategy with annual drama competitions developed with collaboration from the BMCA  Batwa land purchases  VSLA-oriented livelihood program  Vocational skills development for landless livelihoods, particularly with the Batwa  Mgahinga Water program in collaboration with other stakeholders  Bwindi Comprehensive Tea project—integrating PAM, land-use planning, road construction, private public partnerships, and livelihoods  Enhance governance and build a monitoring and evaluation system for both projects and community representation within the Trust Although the BMCA should guide conservation efforts around the park, the Trust can develop these programs listed above together with BMCA stakeholders, which will do much to support local wellbeing and biodiversity conservation for years to come.